KONTRIBUSI SEKTOR UNGGULAN TERHADAP PRODUK DOMESTIK BRUTO KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Radhi, Fahmy; Hariningsih, Endang (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2017)
The purpose of research is to examine how the seed sector contribution to the GRDP Kulon Progo District of Yogyakarta Special Region. The study was conducted by analyzing secondary data time series based on the undertaking of the GRDP from 2009 to 2013.Location Quotient analysis results show featured sector Kulon Progo there are four sectors, namely agriculture, mining and quarrying, manufacturing, and services sectors. Based on Shift-Share analysis, it was concluded that the Construction Sector topped the largest percentage of positive growth, the largest production ratio, and the value of the largest Net Shift in Kulon Progo District. According to the Boston Consulting Group Matrix, the services sector is the only sector of the economy in Kulon Progo which are in quadrant star. So, these services sector need to be maintained in order to increase its policy of high growth rates and contributed greatly to the Kulon Progo GRDP.